2016
DOI: 10.18404/ijemst.02496
|View full text |Cite
|
Sign up to set email alerts
|

Using Data Mining Techniques Examination of the Middle School Students’ Attitude towards Mathematics in the Context of Some Variables

Abstract: The aim of this study is to examine middle school students" attitude towards mathematics in the context of their mathematic learning preferences using data mining which is data analysis methodology that has been successfully used in different areas including educational domains. "How do I actually learn?" questionnaire and attitude scale were applied to 702 middle school students studying in three different cities of Turkey. Demographic data (gender, grade level, parents" education level, pre-school education)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…This is indeed our approach in the current study, relying on logged data from an online, applet-based environment for elementary school mathematics, and analyzing it to study differences in students' behaviors when attempting to solve questions of different thinking levels; the latter variable was collected manually and was triangulated with the data from the log files. As for the importance of age in the context of mathematics education -potentially impacting students' achievements either because of their psychological development or attitudes towards mathematics -and as age was not included in the data we analyzed, the current study includes this variable, mediated by grade level (Idil et al, 2016;Zhou et al, 2019).…”
Section: Log-based Analysis Of Students' Learning In Mathematical Online Learning Environmentsmentioning
confidence: 99%
“…This is indeed our approach in the current study, relying on logged data from an online, applet-based environment for elementary school mathematics, and analyzing it to study differences in students' behaviors when attempting to solve questions of different thinking levels; the latter variable was collected manually and was triangulated with the data from the log files. As for the importance of age in the context of mathematics education -potentially impacting students' achievements either because of their psychological development or attitudes towards mathematics -and as age was not included in the data we analyzed, the current study includes this variable, mediated by grade level (Idil et al, 2016;Zhou et al, 2019).…”
Section: Log-based Analysis Of Students' Learning In Mathematical Online Learning Environmentsmentioning
confidence: 99%
“…According to the results in Table 5, the topics studied in EDM are investigation the causes of students' failures (Baran & Kilic, 2015;Birtil, 2011;Ucgun, 2009), text mining (Afacan Adanir, 2019;Akcapinar, 2015;Sohsah et al, 2015), determination of variables that affect attitude (Hark, 2013;Idil et al, 2016), determination of reasons for absenteeism (Dalkilic & Aydin, 2017), estimation of instructor performance (Cifci et al, 2018), determination of familial variables affecting reading skill (Avsar & Yalcin, 2015), prediction of the department that students will prefer (Coskun, 2013), modeling of video navigations (Akcapinar & Bayazit, 2018) and prediction emotional states with facial recognition and (Ayvaz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…When Table 4 is analyzed, it is observed that 46.77% of the studies are for prediction task, followed by the tasks of classification, clustering and association rules respectively. Yelegin (2012), Saygili (2013), Sengur (2013), Akcapinar (2014), Aksoy (2014), Ozbay (2015), Uysal (2015), Cebi (2016), Sahin (2018), Guruler et al (2010), Sohsah et al (2015), Idil et al (2016), Ayvaz et al (2017), Afacan Adanir (2019) 24.19 Prediction Aydin (2007), Y. Aydogdu (2011), Sengur (2013, Bahadir (2013), Yildiz (2014), Akcapinar (2014), Coskun (2013), Uysal (2015), Yildiz Aybek (2016), Cebi (2016), Barngrover (2017), Yagci (2018), Yorganci (2018), Kentli and Sahin (2011), Turhan et al (2013), Akcapinar (2015), Demir (2015), Kayri (2015), Sohsah et al (2015), Bahadir (2016) Note.…”
Section: Figure 1 Distribution Of Edm Studies Per Year Of Publicationmentioning
confidence: 99%
See 1 more Smart Citation
“…An important research that characterizes students' learning preferences in mathematics is also proposed by Forster (1999). Forster (1999) considers a model according to four fundamental dimensions helping educators to plan learning environments in mathematics course (Idil, Narli & Aksoy, 2016): reflective, inquisitive, diligent, and user.…”
Section: Introductionmentioning
confidence: 99%